Traduttore, traditore: Hebrew RDA as a Septuagint - Ahava Cohen (JLIS.it, 2018)
Hebrew-language resources are widely cataloged throughout the world, but until the era of RDA there had never been an attempt to translate a comprehensive set of cataloging terminology and definitions. Translating the result of centuries of cataloging traditions and of international cooperation into Hebrew is a highly complex task. Aside from the usual issues of grammar, syntax, and orthography, respect must be paid to the pidgin used in professional communication and in Israeli library school cataloging classes. Other factors to be considered include the highly-gendered nature of Hebrew, the effect of Academy of the Hebrew Language decisions on cataloging terminology, and the organizational challenge of translation in a country which has no national policy and standards body and whose librarianship organizations are led by volunteers. This paper will discuss the problems involved in translating RDA terminology into Hebrew as well as the innovations in the Israeli cataloging world being undertaken to facilitate an efficient and timely translation.